Exploring the Role of Culturally Responsive Pedagogy in Promoting Equity Across Diverse Educational Environments - Aina Fahadah; Jame Thomps (International Journal of Post Axial: Futuristic Teaching and Learning, 2025)
This study explores the role of Culturally Responsive Pedagogy (CRP) in promoting equity, student engagement, academic achievement, and inclusivity in diverse educational environments. Through a combination of classroom observations, student and teacher interviews, and focus groups, the research investigates how CRP practices influence students' academic performance, participation, and sense of belonging. The findings reveal that CRP significantly enhances student engagement, particularly among students from marginalized backgrounds, by making learning more relevant to their cultural identities. Furthermore, CRP contributed to improved academic outcomes, particularly in reducing achievement gaps between minority and low-income students. The study also highlights the positive impact of CRP on teacher-student relationships and the overall school climate, fostering an inclusive environment where students feel valued and respected. This research underscores the importance of integrating culturally responsive practices into teaching and policy to promote equity and inclusion in education.